Efektivitas Penerapan Self-Assessment dalam Meningkatkan Keterampilan Berpikir Reflektif Matematis Menggunakan Pembelajaran Collaborative Problem Solving - Latuconsina, Nur Khalisah; Tayeb, Thamrin (Al Asma: Journal of Islamic Education, 2025)
This study aims to test the effectiveness of self-assessment implementation in improving mathematical reflective thinking skills using Collaborative Problem Solving learning. This study is a quasi-experimental study with a non-equivalent pretest-posttest control group design. The population in this study were all students of grade VIII of SMP 4 Sungguminasa. This study involved class VIII-J as the Collaborative Problem Solving group and class VIII-K as the conventional learning group. The instrument used was a reflective thinking ability question in the form of a description. The results of the analysis of the pretest score data found that before being given treatment, both groups had the same initial ability, and the results of the analysis of the posttest score data found that the reflective thinking ability and self-assessment of students who received Collaborative Problem Solving learning were better than students who received conventional learning. The results of this study indicate that Collaborative Problem Solving provides opportunities for students to build their thinking skills. In addition, with self-assessment, students can correct themselves during the learning process. This impacts students' awareness to be better at the next meeting during the learning process.